Isolated Small Bowel Perforation Following Blunt Trauma - Dhayalan, G; Junaidi, AH; Salleh, MS; Aina, K (IIUM Medical Journal Malaysia, 2019)
Small bowel perforation is common following blunt abdominal trauma. Intra-abdominal injury with isolated small bowel perforation however, is a rare entity and diagnosis can be ambiguous. Nonisolated small bowel perforation, which carries a higher mortality rate, will be identified early during the assessment of the patient following a blunt abdominal trauma. A case of an isolated small bowel perforation following a road traffic accident is reported. A motorcycle rider, while trying to avoid a car, lost control and skidded into a drain. Upon arrival to the Emergency Department, he was complaining of upper abdominal pain evident by abrasion and bruising of his bilateral hypochondriacs. FAST scan showed free fluid at Morrison’s pouch and a formal abdominal ultrasound confirmed minimal free fluid at Morrison’s pouch. A plain CT abdomen was done and did not show any evidence of solid organ injury but demonstrated pneumoperitoneum. In view of the persistent abdominal tenderness, open fracture of left femur, radius and ulna, and radiological findings, a laparotomy was performed which revealed an isolated 1x1cm small bowel perforation, 60cm from DJ junction with localized faecal contamination. Small bowel repair was done and patient recovered well afterward. Although challenging, due to its detrimental infectious potential, early recognition of small bowel injury is crucial. Isolated small bowel perforation, rarely without associated intra-abdominal injury, requires more investigations, delaying diagnosis to treatment period. CT abdomen has proven to be both specific and sensitive in diagnosing small bowel injuries. Even when physical examination and radiological examinations are minimal, a suspicion of small bowel perforation should be considered as delay in diagnosis eventually increases morbidity and mortality.